Perbedaan Pengetahuan, Sikap dan Perilaku Ibu dalam Praktik Pemberian MP ASI menggunakan Video Edukasi - Yolahumaroh, Yolahumaroh; Erowati, Dewi; Marlina, Yessi (LPPM Hang Tuah Pekanbaru, 2024)
Introduction: Malnutrition in early life can impact later life. In Indonesia, the determinant cause of malnutrition is inadequate complementary feeding. Lack of knowledge, misguided beliefs, and food taboos are also factors that determine complementary feeding. For this reason, the community needs to be given education about nutrition and health behavior through appropriate IEC. Objectives of the study: To determine the difference in knowledge, attitude, and behavior of mothers in the practice of breastfeeding using Educational Video. Methods: This study is a pre-experimental study with one group pretest and post-test. The study was conducted from January to December 2023 in Pekanbaru City. Results/findings: The results of the Wilcoxon test showed that there was a significant difference between the knowledge variables before and after the provision of educational videos with a value of p = 0.000 (p <0.05) and there was a significant difference between the attitude variables before and after the provision of educational videos with a value of p = 0.000 (p <0.05). but there was no significant difference between the behavior variables before and after the provision of educational videos with a value of p = 0.209 (p>0.05). Conclusion: Education with video media in mothers who have children aged 6-24 months can improve knowledge and attitudes, but there is no difference in maternal behavior in providing complementary food.